NAVIGATING THE COMPLEXITIES OF 60 GHZ 5G WIRELESS COMMUNICATION SYSTEMS AT 60 GHZ FREQUENCY BAND FOR SECURE V2V COMMUNICATION - Maken, Sultan (Nazarbayev University School of Engineering and Digital Sciences, 2024)
Road safety concerns have increased with the rising surge in vehicular traffic and can be tackled by breakthrough solutions. One of such approaches which has drawn much attention is Vehicular-to-Vehicular communication through Massive MIMO at 60 GHz mmWave technology in the 5G spectrum. Massive MIMO utilizes multiple antennas to improve spectral efficiency, throughput, coverage, energy efficiency, and reduce latency. Installation of Massive MIMO for mmWave technology entails greater complexities more so in channel estimation. The problem is solved in this paper as this work designs a sparsity adaptive algorithm that manages the tradeoff between accuracy and computational complexity. The algorithm works for real-time V2V communication taking massive MIMO into consideration and especially for 60 GHz environments. The authors conducted research from which this paper is designed to compare existing channel estimation techniques’ effectiveness in different environments. It offers prospects for improvement in V2V communication hence better road network in the traffic scenario.
Keywords: Type of access: Open Access; Massive MIMO system; V2V communication; 60 GHz frequency band; channel estimation